Speech and swallowing disorders in patients with muscular dystrophy: a systematic review - Leiva, Daniela; Sepúlveda, Carolina; Toledo, Lilian Denisse (Revista de Investigación en Logopedia, 2023)
Muscular dystrophy encompasses a heterogeneous group of muscular disturbances of genetic origin. The purpose of this review was to describe the most common speech and swallowing disorders found in patients with muscular dystrophy. A computer search was carried out to identify relevant articles in this area, which included patients with muscular dystrophy associated with speech and/or swallowing disorders. The databases used were EMBASE, CINAHL, PubMed, PsycInfo, Web of Science, and Scopus. A total of 15 studies met the inclusion criteria, with a total of 526 participants and a mean age of 43.09 years. 12 of the 15 studies included measures for swallowing and/or feeding, and 3/15 included speech evaluations. The review shows a high degree of variability between the instruments used to describe speech and swallowing disorders. Regarding the effects of muscular dystrophy on swallowing, difficulties are observed mainly in the pharyngeal stage as well as with bolus formation, associated with disturbances in occlusion and muscle strength. Speech is a little-studied parameter in this type of condition.
Keywords: dysphagia; dysarthria; Muscular dystrophy